Non-apoptotic programmed cell death with paraptotic-like features in bleomycin-treated plant cells is suppressed by inhibition of ATM/ATR pathways or NtE2F overexpression - Smetana, Ondřej; Široký, Jiří; Houlné, Guy; Opatrný, Zdeněk; Chabouté, Marie-Edith (Journal of Experimental Botany, 2012)
In plants, different forms of programmed cell death (PCD) have been identified, but they only partially correspond to those described for animals, which is most probably due to structural differences between animal and plant cells. Here, the results show that in tobacco BY-2 cells, bleomycin (BLM), an inducer of double-strand breaks (DSBs), triggers a novel type of non-apoptotic PCD with paraptotic-like features. Analysis of numerous PCD markers revealed an extensive vacuolization, vacuolar rupture, and chromatin condensation, but no apoptotic DNA fragmentation, fragmentation of the nuclei, or sensitivity to caspase inhibitors. BLM-induced PCD was cell cycle regulated, occurring predominantly upon G(2)/M cell cycle checkpoint activation. In addition, this paraptotic-like PCD was at least partially inhibited by caffeine, a known inhibitor of DNA damage sensor kinases ATM and ATR. Interestingly, overexpression of one NtE2F transcriptional factor, whose homologues play a dual role in animal apoptosis and DNA repair, reduced PCD induction and modulated G(2)/M checkpoint activation in BY-2 cells. These observations provide a solid ground for further investigations into the paraptotic-like PCD in plants, which might represent an ancestral non-apoptotic form of PCD conserved among animals, protists, and plants.
Keywords: E2F Transcription Factors; DNA Fragmentation; fragmentace DNA; Plant Proteins; transkripční faktory E2F; Nicotiana; Cell Cycle Checkpoints; kontrolní body buněčného cyklu; Protein Serine-Threonine Kinases; Bleomycin; rostlinné proteiny; buněčná smrt; Down-Regulation; Cell Death; exprese genu; down regulace; tabák; protein-serin-threoninkinasy; bleomycin; Gene Expression